A systematic review of the relationship between rigidity/flexibility and transdiagnostic cognitive and behavioral processes that maintain psychopathology. Issue 3 (11th July 2018) - Morris, Lydia; Mansell, Warren
An ever-growing number of transdiagnostic processes that maintain psychopathology across disorders have been identified. However, such processes are not consistently associated with psychological distress and symptoms. An understanding of what makes such processes pathological is required. One possibility is that individual differences in rigidity in the implementation of these processes determine the degree of psychopathology. The aim of this article is to examine the relationship between rigidity/flexibility and transdiagnostic maintenance processes. Initial searches were made for research examining relationships between 18 transdiagnostic processes and rigidity/flexibility. Relationships between rumination, perfectionism, impulsivity and compulsivity, and rigidity/flexibility were systemically reviewed; 50 studies met inclusion criteria. The majority of studies indicated that transdiagnostic cognitive and behavioral maintenance processes and rigidity were correlated, co-occurring, or predictive of each other. Findings are consistent with the hypothesis that it is inflexibility in the manner in which processes are employed that makes them pathologically problematic. However, further research is required to test and establish this.